Trilemma Hypothesis: A Different Perspective on Turkey Economy - Havva Koç (İstanbul İktisat Dergisi)
The Trilemma Hypothesis continues to provide a macroeconomic framework with the trade-offs and challenges faced by policymakers, investors, and central banks. The Trilemma Hypothesis starting with Mundell-Fleming and developed by Frankel shows that in an open economy, the monetary authority cannot apply three policies simultaneously to achieve economic goals. It is important to examine the preferred economic policy in the short run in Turkey within the framework of the Trilemma Hypothesis. It aims to analyze the effect of the real effectiveexchange rate and total funding imposed by the Central Bank on net international investment position, direct investments, and portfolio investments during the period 2011Q2-2020Q2 in Turkey. The long-term relationship between variables was estimated by using the ARDL method. Findings of the study suggest that the Trilemma Hypothesis is valid for Turkey. In this study, choosing the central bank total funding rate as an expansionary monetary policy is of particular importance as it has not been encountered in the literature. In this context, it is thought that this original study can contribute to the literature.